2020
DOI: 10.1128/mra.00226-20
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Six Type Strains of the Genus Massilia

Abstract: High-quality draft genome sequences were determined for 6 Massilia sp. type strains. The genomes of these strains show considerable biosynthetic potential for producing secondary metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Recently, the antibacterial activity of Massilia species via soluble compounds was described against two Gram-negative pathogens (Dahal et al 2021). Numerous biosynthetic gene clusters found in Massilia species suggesting them as a source for novel antimicrobial compounds (Miess et al 2020). Our results expand the knowledge about Massilia's antimicrobial potential to volatile emitted compounds.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, the antibacterial activity of Massilia species via soluble compounds was described against two Gram-negative pathogens (Dahal et al 2021). Numerous biosynthetic gene clusters found in Massilia species suggesting them as a source for novel antimicrobial compounds (Miess et al 2020). Our results expand the knowledge about Massilia's antimicrobial potential to volatile emitted compounds.…”
Section: Discussionsupporting
confidence: 59%
“…The β-proteobacterial genus Massilia was recently identified as an untapped reservoir of novel natural products [ 15 ]. In particular, the strain Massilia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Violacein and deoxyviolacein are known to be produced by various Gram-negative bacteria, including from the genus Chromobacterium [22], Collimonas [23], Duganella [14], Massilia [24], Pseudoalteromonas [19,25], and Janthinobacterium [26]. The production of these compounds varies between species, and previous works showed that media composition [27,28] and culture conditions [27,29] could significantly affect violacein production in different bacterial strains.…”
Section: Introductionmentioning
confidence: 99%